A fundamental study on styles of Malaysian contemporary ceramic art from 1959-2009 / Muliyadi Mahmood … [et_al.] - Mahmood, Muliyadi; Adam, Tajul Ariffin; Mohd. Aris, Khairul Nizan; Yahya, Syed Yusainee (Research Management Institute (RMI), 2010)
Thus research is neither a historical study nor a compilation of artists itself but more on finding the style in contemporary ceramic in Malaysia and what factors that influence it; a first attempt documenting artworks of contemporary ceramic in Malaysia. Fourty-three artworks of thirty-five various artist from pioneer of ceramic art to the modern young artist that were produced for the past five decades were chosen and analyzed in this study. This is an art historical study on the question of style. It is based on the theory of style by Schapiro and Ackerman who stated that style refers to the formal qualities and visual characteristics of a piece of art. Four elements that have been identified based on the Theory of Art Criticism by Edmund.B.Feldman which are described, analyze, interpret, and evaluate the form, function, content and context in each artwork are determine to identify the National Identifiable Style to represent Malaysian Contemporary Ceramic Art. Factors that influenced the artists are determined based on the Theory of Cuture by Edward Burnett Tylor (1871), who stated that culture or civilization, taken in its wide ethnographic sense, is that complex whole which includes knowledge, belief art, morals, law, custom, and any other capabilities and habits acquired by man as a member of society